Przedstaw trójmian w postaci ogólnej

y=2(x-4)(x+1)

y=-(x+5)(x-4)

y=2(x-2)2

y=-6(x+1)2



Odpowiedź :

Cześć!

Postać ogólna funkcji kwadratowej

[tex]y=ax^2+bx+c[/tex]

1)

[tex]y=2(x-4)(x+1)\\\\y=2(x^2+x\cdot1-4\cdot x-4\cdot1)\\\\y=2(x^2+x-4x-4)\\\\y=2(x^2-3x-4)\\\\y=2\cdot x^2-2\cdot3x-2\cdot4\\\\\huge\boxed{y=2x^2-6x-8}[/tex]

2)

[tex]y=-(x+5)(x-4)\\\\y=-(x\cdot x-x\cdot4+5\cdot x-5\cdot4)\\\\y=-(x^2-4x+5x-20)\\\\y=-(x^2+x-20)\\\\\huge\boxed{y=-x^2-x+20}[/tex]

3)

[tex]y=2(x-2)^2\\\\y=2(x^2-2\cdot x\cdot2+2^2)\\\\y=2(x^2-4x+4)\\\\y=2\cdot x^2-2\cdot4x+2\cdot4\\\\\huge\boxed{y=2x^2-8x+8}[/tex]

Użyty wzór skróconego mnożenia

[tex](a-b)^2=a^2-2ab+b^2[/tex]

4)

[tex]y=-6(x+1)^2\\\\y=-6(x^2+2\cdot x\cdot1+1^2)\\\\y=-6(x^2+2x+1)\\\\y=-6\cdot x^2-6\cdot2x-6\cdot1\\\\\huge\boxed{y=-6x^2-12x-6}[/tex]

Użyty wzór skróconego mnożenia

[tex](a+b)^2=a^2+2ab+b^2[/tex]